Ambiguity of crustal geotherms: A thermal-conductivity perspective. (January 2021) - Förster, A.; Fuchs, S.; Förster, H.-J.; Norden, B.
Highlights: Relations of P–T dependence of rock thermal conductivity derived from PCM and the LFA are used for geotherm calculation. Deviation between uncorrected and P–T corrected geotherms is minor for surface heat flow qs <40 mW m –2 . Deviation increases with higher qs and may exceed some 100 K at the crust–mantle boundary. PCM correction implies higher crustal T relative to those derived from a combined LFA/PCM correction. Abstract: The paper addresses the effects of pressure (P) and temperature (T) on thermal conductivity (λ) applied to crustal geotherms. A subset of the ca. 50 experimentally derived numerical P―T relations available in literature for typical crustal rock types was selected for this purpose. The relations comprise those from physical-contact laboratory methods (PCM), for P and T, as well as from a non-contact technique, the laser-flash analysis (LFA), for T. The effects on geotherms are quantified for two crustal models: (I) a simplified two-layer "Proterozoic" crust, which consists of granitic rocks in the upper part and granulitic rocks in the lower part and (II) a multi-layer "Phanerozoic" crust. We show that neglecting P–T correction of ambient λ leads to underestimation of T that is larger with increasing surface heat flow (qs ). In the Phanerozoic crust, the T difference at the crust–mantle boundary is 130/50 K [PCM/LFA], for qs 60 mW m –2, and 240/100 K, for qs 80 mW m –2 . In the Proterozoic crust, with qs typically <60 mW m –2, the T difference between P–T-corrected versus uncorrected geotherms is minor (55/55 K). The T uncertainty shown by the envelope of min–max solutions of λ correction differs with respect to type of crust and typical heat flow. Lower values (max. < 20/<10 K) are inferred for Proterozoic crust and low to moderate qs (<60 mW m –2 ) compared to the compositionally complex Phanerozoic-type crust (about 210/110 K) with typical qs of 80 mW m –2 . A combined LFA(T)/PCM(P) correction of λ provides lower T than a P–T correction with PCM alone.